Violations of early cardiac morphogenesis under conditions of administration of lead acetate. - G. V. Dovgal; I. V. Shevchenko (Морфологія, 2018)
Background. Lead compounds cause marked nonspecific morphofunctional changes in the vascular system. The negative influence of lead on the microcirculatory bed of the heart is established. In acute intoxication, first compensatory hypertrophy of the myocardium occurs, and in chronic cases structural changes in the form of a decrease in heart mass and left ventricular mass, development of uneven dilatation of the ventricular cavities, restructuring of the vascular bed and development of connective tissue. Objective. The study of histological and morphometric changes in the heart in the early postnatal period of development under conditions of administration of lead acetate. Methods. The effect of lead acetate on cardiac morphogenesis was modeled by administering the solution to pregnant animals intragastrically through the probe once a day throughout the gestation period. Animals of the study group received a 2.5% aqueous solution of lead acetate at a rate of 50 mg/kg of rat body weight per day. The females of the control group received distilled water. At 1, 5 and 7 days after birth, offspring were seized for the study of the morphogenesis of the heart. The heart was drawn and fixed in a 10% formalin solution. Samples were made from histological sections and stained with hematoxylin and eosin. Morphometry of the heart was performed using software. The statistical evaluation was carried out using nonparametric methods. The Kolmogorov-Smirnov test. Intergroup difference was determined by the Kruskal-Wallis criterion. Results. The structural basis of the disturbed morphogenesis is toxic damage to the myocardium and endocardium, which consisted in cell death and reduction of the cellular composition in the corresponding walls of the heart. At the same time, the increased density of nuclei in various phases of mitosis was recorded in the ventricular myocardium, which can be evaluated as a manifestation of regenerative processes. Such results indicate the polymorphism of the morphology of cardiomyocytes, the expansion of the vessels of the microcirculatory bed, as well as the considerable proliferation of connective tissue in the wall of the vessels and between the muscle fibers, and rarely mark the infiltration of leukocytes. Сonclusion. Morphological manifestations of dystrophic changes and initiation of the inflammatory reaction were revealed, and lesions were nonspecific for the atrium and ventricle and mainly consisted of interstitial edema.